2016
DOI: 10.2528/pierc15070105
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Wearable Fractal Antenna for Military Applications at VHF Band

Abstract: Abstract-This paper presents the design and development of Koch fractal dipole antenna for wearable applications at 450 MHz. Common jeans cotton is used as a flexible substrate material having a dielectric constant of 1.6 for the design and fabrication of the proposed antenna. Increasing the number of iterations increases the number of sections, which eventually results in 32% reduction in size. Size miniaturization is obtained using second iteration Koch geometry with the antenna bandwidth of 10%, and the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The peak SAR 1g resulted equal to 0.0252 W/kg and 0.175 W/kg for f = 1.575 GHz and 915 MHz, respectively, both at 1 W input power. Poonkuzhali et al [ 33 ] modelled an antenna on a human arm operating at 1 W input power at 450 MHz and found a peak SAR equal to 0.1427 W/kg. An E-shaped patch wearable textile antenna was considered in [ 34 ] and it was positioned on a torso model; in this study, the peak SAR 1g for f = 1.85 GHz and f = 2.45 GHz, with the input power of 1 W, resulted equal to 0.54 W/kg and 0.35 W/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The peak SAR 1g resulted equal to 0.0252 W/kg and 0.175 W/kg for f = 1.575 GHz and 915 MHz, respectively, both at 1 W input power. Poonkuzhali et al [ 33 ] modelled an antenna on a human arm operating at 1 W input power at 450 MHz and found a peak SAR equal to 0.1427 W/kg. An E-shaped patch wearable textile antenna was considered in [ 34 ] and it was positioned on a torso model; in this study, the peak SAR 1g for f = 1.85 GHz and f = 2.45 GHz, with the input power of 1 W, resulted equal to 0.54 W/kg and 0.35 W/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For high performance radio LAN (HIPER-LAN) applications, the radiation performance of copperbased and Zelt-based conductive fabric-based wearable patch antennas [24] aided by polyester fabric substrate was investigated. Under bending and crumpling conditions, the copper foil koch fractal wearable dipole antenna in the very high frequency (VHF) band (430 MHz-475 MHz) for military applications [25] and the ring resonator wearable patch antenna [27] at 5.8 GHz aided with a common jeans cotton substrate were investigated. A parametric study was demonstrated on the rectangular textile patch antenna [26], which was made from both copper and nickel-plated polyester fabric with a denim substrate for ISM band wireless body-area network applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since the wearable devices are often integrated into the user's clothing, the wearable antenna must be lightweight, thin, easily integrated into the garment, and it should not obstruct the user's movements [7]. Moreover, the position of the antenna relative to the human body is a crucial aspect since, because of that, the wearable device may vary from its original setting and consequently, its performances could change.…”
Section: Introductionmentioning
confidence: 99%